The Effectiveness of Auricular Acupressure in Reducing Post-Surgical Anxiety and Pain in Hemorrhoidectomy Patients: A Randomized Controlled Trial - Qiong Pan, Feifei Shen, Wei Wei Niu, Hong Lu, Elsayed Mohammad Hassan Soliman Attia (South Eastern European Journal of Public Health, 2025)
Introduction: Hemorrhoids, particularly mixed hemorrhoids, are common anorectal diseases causing significant discomfort. Surgical intervention, often necessary for advanced stages, induces preoperative anxiety that can negatively impact recovery. Traditional Chinese medicine (TCM) suggests that auricular acupressure can alleviate anxiety by stimulating specific ear acupoints, thus promoting emotional and physiological balance. Objectives: Despite promising results in various contexts, no scientific study has yet explored the effectiveness of auricular acupressure in reducing post-surgical anxiety and pain in hemorrhoid patients. Methods: This randomized controlled trial involved 132 patients undergoing mixed hemorrhoidectomy. Participants were assigned to either a control group, receiving standard postoperative care, or an experimental group that also received auricular acupressure targeting acupoints such as Shenmen and Endocrine. Anxiety and pain were assessed using the State Anxiety Inventory (S-AI) and Visual Analog Scale (VAS) at multiple time points: pre-intervention, 24, 48, and 72 hours, and 7 days post-intervention. Results: Statistical analysis revealed that the experimental group experienced significantly lower anxiety and pain scores compared to the control group (P < 0.001). Over time, both groups showed a decrease in anxiety and pain, but the experimental group demonstrated superior outcomes across all time points. Conclusions: Auricular acupressure is an effective non-invasive intervention for reducing post-surgical anxiety and pain in hemorrhoidectomy patients. These findings support the integration of TCM techniques with conventional postoperative care, offering a holistic approach to patient recovery. Further research is recommended to explore its broader applications.